1999
DOI: 10.1093/ajcn/69.1.80
|View full text |Cite
|
Sign up to set email alerts
|

Effect of daily and weekly micronutrient supplementation on micronutrient deficiencies and growth in young Vietnamese children

Abstract: Background: Micronutrient deficiencies remain common in preschool children in developing countries. Interventions focus on single micronutrients and often lack effectiveness. Weekly instead of daily supplementation may improve effectiveness. Objective: The efficacy of weekly and daily supplementation in reducing anemia prevalence and in improving the zinc, vitamin A, and growth status of 6-24-mo-old Vietnamese children was investigated. Design: In this double-blind, placebo-controlled trial, the daily group (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
3
18

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 25 publications
5
74
3
18
Order By: Relevance
“…This important improvement helped reduce by 1/3, in only 4 months, the prevalence of anemia (from 41% to 17%) in the total sample, and tended to control and prevent the deficiency, depending on compliance. This reduction to more than half the initial prevalence of anemia agrees with weekly supplementation studies in pre-school children conducted in Brazil 4,11 and in other developing countries 9,10,14,15 . The pioneering study with Chinese pre-school children 8 showed that the correction of hemoglobin levels attained 100%.…”
Section: Discussionsupporting
confidence: 85%
“…This important improvement helped reduce by 1/3, in only 4 months, the prevalence of anemia (from 41% to 17%) in the total sample, and tended to control and prevent the deficiency, depending on compliance. This reduction to more than half the initial prevalence of anemia agrees with weekly supplementation studies in pre-school children conducted in Brazil 4,11 and in other developing countries 9,10,14,15 . The pioneering study with Chinese pre-school children 8 showed that the correction of hemoglobin levels attained 100%.…”
Section: Discussionsupporting
confidence: 85%
“…An earlier trial in Guatemala found that supplementation with zinc alone increased the growth of stunted, but not of non-stunted, infants (Rivera et al, 1998), findings which are consistent with the results of a meta-analysis of the effect of zinc supplementation on children's growth (Brown et al, 2002). Other studies of multiple micronutrients (MMN) found positive effects of supplementation on growth among Mexican (Rivera et al, 2001) and Vietnamese (Thu et al, 1999;Hop and Berger, 2005) infants and among older children in Tanzania (Ash et al, 2003), suggesting that deficiency of one or more these micronutrients was limiting their physical development. Contrary to these results, multiple micronutrient (MMN) supplements did not affect the growth of children in other settings (Penny et al, 2004;Ló pez de Romaña et al, 2005;Smuts et al, 2005;Untoro et al, 2005), possibly because the study subjects were less growth restricted initially, they were not lacking in any of the specific micronutrients that are critical for growth, or the supplements that were provided were poorly absorbed.…”
Section: Introductionsupporting
confidence: 76%
“…Positive effects on growth were observed among infants o12 months of age -but not among older children -in a recent study in Mexico, in which supplements were provided for 1 year (Rivera et al, 2001). MMN supplementation spurred increased growth among 6-to 24-month-old Vietnamese children who were stunted at baseline, but not among those who were non-stunted, in one study (Thu et al, 1999); and daily MMN supplements, but not weekly MMN supplements increased growth of young Vietnamese children in another study (Hop and Berger 2005). Among Tanzanian school children 6-11 years of age, an MMN-fortified drink increased rates of both linear growth and weight gain (Ash et al, 2003).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This positive effect of zinc or iron supplements on knee-heel length is not shown in the former study carried out in the same country (Dijkhuizen et al, 2001). A study conducted in 6 to 24-month-old Vietnamese children concludes that 3-month daily micronutrient supplementation containing zinc had no effect on linear growth of the complete sample of subjects but a positive impact on HAZ of children who were stunted before supplementation (Thu et al, 1999). Another study shows the positive effect of zinc supplementation on plasma IGF-1, an indicator of growth activity, and on linear growth in stunted 4 to 36-month-old Vietnamese children (Ninh et al, 1996) whereas the study conducted in 4-month-old Indonesian infants shows no effect of zinc or iron supplementation on plasma IGF-1.…”
Section: Discussionmentioning
confidence: 72%